2000
DOI: 10.1152/physrev.2000.80.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serine/Threonine Protein Phosphatases on Ion Channels in Excitable Membranes

Abstract: This review deals with the influence of serine/threonine-specific protein phosphatases on the function of ion channels in the plasma membrane of excitable tissues. Particular focus is given to developments of the past decade. Most of the electrophysiological experiments have been performed with protein phosphatase inhibitors. Therefore, a synopsis is required incorporating issues from biochemistry, pharmacology, and electrophysiology. First, we summarize the structural and biochemical properties of protein pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
264
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(276 citation statements)
references
References 451 publications
(475 reference statements)
9
264
3
Order By: Relevance
“…1, A-C). Okadaic acid is a potent inhibitor of both PP1 and PP2A, but 100-fold more potent for PP2A than for PP1 (IC 50 value is 10 -270 and 0.2-2 nM for PP1 and PP2A, respectively) (11,18,19). Therefore, the inability of low dose okadaic acid to enhance mGluR7 phosphorylation suggests that Ser-862 of mGluR7 is a target of PP1 rather than PP2A.…”
Section: Ser/thr Protein Phosphatase 1 Regulates Ser-862mentioning
confidence: 99%
See 1 more Smart Citation
“…1, A-C). Okadaic acid is a potent inhibitor of both PP1 and PP2A, but 100-fold more potent for PP2A than for PP1 (IC 50 value is 10 -270 and 0.2-2 nM for PP1 and PP2A, respectively) (11,18,19). Therefore, the inability of low dose okadaic acid to enhance mGluR7 phosphorylation suggests that Ser-862 of mGluR7 is a target of PP1 rather than PP2A.…”
Section: Ser/thr Protein Phosphatase 1 Regulates Ser-862mentioning
confidence: 99%
“…Similar to protein kinases, protein phosphatases actively participate in regulating synaptic changes and the activity-dependent alterations of synaptic transmission (11,12). It is clear that PKC dramatically regulates mGluR7 trafficking, but the phosphatase(s) that target mGluR7 remain unknown.…”
mentioning
confidence: 99%
“…Kinases play important, well documented, roles in the regulation of numerous cellular functions [10,43,67]. The physiological significance of serine/threonine protein phosphatases has also been appreciated, and these enzymes have been implicated in the regulation of ion channels, synaptic plasticity, exocytosis, and apoptosis [31,36,58,70].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, when 2 luciferase reporter assays were employed to test whether PP4 regulates IL-2 transcriptions, we found that the inhibition of PP2A/PP4/PP6 by OA failed to reduce the activity of IL-2 promoter (Fig. 4D) even at a relatively high dose of 50 nM, 25 hinting that PP4 deficient may not significantly alter IL-2 transcription. Combined with the mixed proliferation data (Fig.…”
Section: Pp4 Deficiency Induces G1-s Blocks and Retards T Cell Prolifmentioning
confidence: 95%
“…3 Treatment with OA (and the resulting suppression of PP2A, PP4 and PP6) has been reported to down-regulate the mRNA level of IL-2 25 through multiple pathways. 27,31 In addition, our data showed that activated PP4-deficient T cells produced significantly less IL-2 (p D 0.007) (as well as IL-4 and IL-10) ( Fig.…”
Section: Pp4 Deficiency Induces G1-s Blocks and Retards T Cell Prolifmentioning
confidence: 99%